2013
DOI: 10.1242/jeb.094649
|View full text |Cite
|
Sign up to set email alerts
|

Urea-based osmoregulation in the developing embryo of oviparous cartilaginous fish (Callorhinchus milii): contribution of the extraembryonic yolk sac during the early developmental period

Abstract: Marine cartilaginous fish retain a high concentration of urea to maintain the plasma slightly hyperosmotic to the surrounding seawater. In adult fish, urea is produced by hepatic and extrahepatic ornithine urea cycles (OUCs). However, little is known about the urea retention mechanism in developing cartilaginous fish embryos. In order to address the question as to the mechanism of urea-based osmoregulation in developing embryos, the present study examined the gene expression profiles of OUC enzymes in oviparou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…The analysis of the spiny dogfish transcriptome reveals the presence of all the genes involved in the two main biosynthetic pathways for urea synthesis in cartilaginous fishes ( Table 5 ) and as expected, all of these genes are expressed in the liver, the main tissue involved in urea synthesis. However, in accordance with previous studies [ 6 8 , 58 ] some of the urea synthesis genes were identified in extra-hepatic tissues as well.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of the spiny dogfish transcriptome reveals the presence of all the genes involved in the two main biosynthetic pathways for urea synthesis in cartilaginous fishes ( Table 5 ) and as expected, all of these genes are expressed in the liver, the main tissue involved in urea synthesis. However, in accordance with previous studies [ 6 8 , 58 ] some of the urea synthesis genes were identified in extra-hepatic tissues as well.…”
Section: Discussionsupporting
confidence: 91%
“…The egg capsules were opened and embryos were removed from the yolk sacs. Mean weights and days post-egg laying at each developmental stage were described previously (Takagi et al, 2014). Embryos were staged according to Didier et al (1998) Redrawn from Kuratani (1997).…”
Section: Materials and Methods Embryosmentioning
confidence: 99%
“…The absolute quantification of target mRNAs was performed by qPCR with an ABI Prism 7900HT Sequence Detection System (Life Technologies, Carlsbad, CA, USA) and KAPA SYBR FAST ABI Prism qPCR Kit (Kapa Biosystems), as previously described (Takagi et al, 2014). The results were shown either as normalized by -actin or as the copy number of target mRNAs per gram of RNA.…”
Section: -4 Tissue Distributionmentioning
confidence: 99%
“…A breakthrough in chondrichthyan biology was achieved by Venkatesh and colleagues, who initiated whole genome sequencing for the holocephalan elephant fish (or elephant shark, Callorhinchus milii) (http://esharkgenome.imcb.a-star.edu.sg/) (Venkatesh et al, 2007). We have focused on this species as a model for molecular endocrinological and physiological studies of cartilaginous fish (Hyodo et al, 2007;Kakumura et al, 2009;Yamaguchi et al, 2012;Takagi et al, 2014). Recently, a PRL-like gene was found from the elephant fish genome and designated PRL2 (Huang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%